PELATIHAN SDM PENYEDIA PELAYANAN PENANGANAN KEKERASAN TERHADAP PEREMPUAN - Prihatin (Akademi Maritim Nusantara Banjarmasin, 2023)
AbstractWomen certainly cannot be separated from physical and psychological problems. From a physical point of viewit is based on the biological structure, composition and development of the chemical elements of the body. While the psychic pointof view is based on nature, masculinity or femininity. Women in the psychological or gender context are definedas traits thatare inherent in someone to be feminism.Invitation to activities as participants aimed at increasing the capacity of the resources of institutions thatprovide treatment for women victims of violence at the district/city authority through the field of women's protection who haveorganized training activities for human resources for women's protection, which were carried out for three days, Monday29-Wednesday 31 May 2023, in the Central Banjarmasin district hall, Jl. Pulau Laut Antasan Besar, CentralBanjarmasin. Banjarmasin city.Results of HR Training for Service Providers for Handling Violence Against Women as one of the services tothe community, of course providing protection to women and children in dealing with problems of violence both in thehousehold or other environments to eradicate violence for anyone, especially women and children. The three days oftrainingprovided a lot of knowledge that previously did not know much about the details, but now they know more about the lawand how to deal with these situations according to the applicable stages. Thus, in this training almost all women asknowledge and rules must be upheld and cannot remain silent if they know something suspicious.Keywords: Human Source Department, Service, Women